The Role of Mitogen-Activated Protein Kinase-Activated Protein Kinases (MAPKAPKs) in Inflammation - Ugo Moens (Genes, 2013)
Mitogen-activated protein kinase (MAPK) pathways are implicated in several cellular processes including proliferation, differentiation, apoptosis, cell survival, cell motility, metabolism, stress response and inflammation. MAPK pathways transmit and convert a plethora of extracellular signals by three consecutive phosphorylation events involving a MAPK kinase kinase, a MAPK kinase, and a MAPK. In turn MAPKs phosphorylate substrates, including other protein kinases referred to as MAPK-activated protein kinases (MAPKAPKs). Eleven mammalian MAPKAPKs have been identified: ribosomal-S6-kinases (RSK1-4), mitogen- and stress-activated kinases (MSK1-2), MAPK-interacting kinases (MNK1-2), MAPKAPK-2 (MK2), MAPKAPK-3 (MK3), and MAPKAPK-5 (MK5). The role of these MAPKAPKs in inflammation will be reviewed.